Pragmatic Believing and its Explanation - Ward E. Jones (Crítica)
Most explanations of beliefs are epistemically or pragmatically rationalizing. The distinction between these two types involves the explainer's differing expectations of how the believer will behave in the face of counterevidence. This feature suggests that rationalizing explanations portray beliefs as either (i) a consequence of the believer's following a norm, or (ii) part of a sub-intentional goal-oriented system. Which properly characterizes pragmatic believing? If there were pragmatic norms for believing, I argue, they would not be consciously followable. Yet an unfollowable norm is not a norm at all, and so I conclude that there are no such norms and that pragmatic believing is a sub-intentional, and not a norm-driven, process.